Three new species of Stictane Hampson, 1900 (Erebidae, Arctiinae) from Cambodia, with Checklist of Stictane - Bayarsaikhan, Ulziijargal; Bae, Yang-Seop (Zootaxa, 2015)
Genus Stictane Hampson is reviewed in Cambodia, with seven species treated. Of them, S. cambodiensis Bae & Bayarsaikhan, n. sp., S. khmerensis Bae & Bayarsaikhan, n. sp., and S. bokorensis Bayarsaikhan & Bae, n. sp. are described as new to science. S. pectinata Holloway, 2001, S. mlcochi Bucsek, 2012, and S. fuscus Bucsek, 2014, are newly recorded from Cambodia. Up to now unknown female of S. fuscus, is firstly described. The following three species are newly combined: S. munda (de Joannis, 1928) comb. nov.; S. paucilinea (de Joannis, 1928) comb. nov.; and S. umbrimedia (de Joannis, 1928) comb. nov. Illustrations of adults and genitalia are provided, with a checklist of the genus Stictane.